Human behavioural discrimination of human, chimpanzee and macaque affective vocalisations is reflected by the neural response in the superior temporal sulcus. (March 2018) - Fritz, Thomas; Mueller, Karsten; Guha, Anika; Gouws, Andre; Levita, Liat; Andrews, Timothy J.; Slocombe, Katie E.
Abstract: Accurate perception of the emotional content of vocalisations is essential for successful social communication and interaction. However, it is not clear whether our ability to perceive emotional cues from vocal signals is specific to human signals, or can be applied to other species' vocalisations. Here, we address this issue by evaluating the perception and neural response to affective vocalisations from different primate species (humans, chimpanzees and macaques). We found that the ability of human participants to discriminate emotional valence varied as a function of phylogenetic distance between species. Participants were most accurate at discriminating the emotional valence of human vocalisations, followed by chimpanzee vocalisations. They were, however, unable to accurately discriminate the valence of macaque vocalisations. Next, we used fMRI to compare human brain responses to human, chimpanzee and macaque vocalisations. We found that regions in the superior temporal lobe that are closely associated with the perception of complex auditory signals, showed a graded response to affective vocalisations from different species with the largest response to human vocalisations, an intermediate response to chimpanzees, and the smallest response to macaques. Together, these results suggest that neural correlates of differences in the perception of different primate affective vocalisations are found in auditory regions of the human brain and correspond to the phylogenetic distances between the species. Highlights: Perception and neural response to vocalisations from humans, chimpanzees and macaques. Discrimination of emotional valence varied with phylogenetic distance. Neural responses in superior temporal sulcus varied with phylogenetic distance.